Anticipating antimatter?. Issue 2 (1st April 2018) - Taylor, Christopher
Abstract : Christopher Taylor was surprised to find discussion of antimatter in 1898. Abstract : Christopher Taylor was surprised to find a speculative discussion of antimatter and the origin of the universe in 1898.